A novel STAT3 inhibitor HO-3867 induces cell apoptosis by reactive oxygen species-dependent endoplasmic reticulum stress in human pancreatic cancer cells. Issue 4 (April 2017) - Hu, Yan; Zhao, Chengguang; Zheng, Hailun; Lu, Kongqin; Shi, Dengjian; Liu, Zhiguo; Dai, Xuanxuan; Zhang, Yi; Zhang, Xiuhua; Hu, Wanle; Liang, Guang
Abstract : Pancreatic cancer is the most commonly diagnosed malignancy among solid tumors and has shown an increasing trend year by year. Thus, there is an urgent need for the discovery of new anticancer drugs for the treatment of pancreatic cancer. In recent years, it has been reported that the compound HO-3867, a novel analog of the natural product curcumin, showed antitumor activity with low toxicity. However, the underlying mechanism of this compound's attack on cancer cells is not very clear. In the present study, it was found that HO-3867 showed good antitumor activity at the concentration of 2 μmol/l in PANC-1 and BXPC-3 cells. Importantly, it was also found that HO-3867 treatment significantly induced reactive oxygen species (ROS) production in human pancreatic cancer cell lines, inducing PANC-1 and BXPC-3 cells. Co-treatment with the ROS scavenger, N -acetyl cysteine, partially abrogated HO-3867-induced cell apoptosis. The activation of mitogen-activated protein kinase and endoplasmic reticulum stress indicated a downstream event of ROS generation in mediating the anticancer effect of the HO-3867. In addition, independent of the ROS pathway, direct STAT3 inhibition was observed in HO-3867-induced cell apoptosis. Taken together, the results of this work suggest that both the ROS-dependent ER stress and STAT3 pathways were implicated in the cell apoptosis induced by the novel compound HO-3867.